Pendidikan Akhlaq Aplikatif-Integratif pada Madrasah Ibtidaiyah di Rubaru Sumenep - Ummi Kulsum (Tafhim Al-'Ilmi, 2020)
Education of moral is education that is very important to instill moraland spiritual values in life that can foster character, behavior, and good moralsfor future. If education of moral is not instilled in students from an early age, itdoes not close the possibility that students will fall into something that is notdesired by the wider community. Research on "applicative-integrative educationof moral in Madrasah Ibtidaiya Rubaru Sumenep" was carried out because it wasbased on these concerns.This research used descriptive-qualitative method with aphenomenological approach, which is by going down directly to the researchlocation to search for the data needed. As for this study the population taken wasthe whole of students of Madrasah Ibtidaiyah Rubaru Sumenep in the 2018-2019Academic year by giving a number of questions to students randomly by means ofrandom sampling. The respondents I chose were students in grades 4, 5, and 6 ofMI Nurus Salam Pakondang Village, Rubaru District, Sumenep Regency. So thetotal sample that will be in the data amounted to 35 students. Primary datasources in this study were the results of interviews with school principals, vicecurriculim, and moral teachers in MI Nurus Salam, Pakondang village, Rubarusub-district, Sumenep district.The results showed a strong commitment from MI Nurus Salam torealize an applicative-integrative moral education in the sense that morallearning does not stop in the area of the concept of knowledge about morals, butthere are efforts to internalize, habituate, exemplify, and continue coaching.Moral development implemented at MI Nurus Salam includes twothings: First, by guiding moral behavior through religious activities, such asreciting Asmaul Husna, Yasin letter, followed by Duha prayer 30 minutes beforeentering class and reading short letters 10 minutes before the lesson begins. Thisactivity is a routine activity that must be followed by every student from grade 1 tograde 6.Second, Commemoration of Islamic holidays (PHBI), such as the Birthof the Prophet, Isra ’Mi'raj,‘ Ashura, and Ramadan activities, all of theseactivities as a medium in fostering student morals. In implementing thisapplicative-integrative moral education, all parties are involved in the routinecoordination and monitoring of moral behavior. As a form of evaluation, thevalue of moral behavior in MI Nurus Salam is coordinated by the homeroomteacher as a report card on the behavior, crafts and neatness based on reportsfrom each teacher